Methotrexate induced lung injury in a patient with primary CNS lymphoma : A case report - puneet chhabra; arjun dutt law; dr vikas suri; dr pankaj malhotra; dr subhash varma (Mediterranean Journal of Hematology and Infectious Diseases, 2012)
Methotrexate is an antimetabolite commonly used in clinical practice for a variety of indications ranging from rheumatoid arthritis and other connective tissue disorders to high dose regimens in many malignancies. This folate antagonist has got a spectrum of toxicities among which gastrointestinal effects predominate . Lung injury is a well described but rare event and has been reported most often in patients who have been on long term oral therapy for rheumatic disorders. Acute lung injury in a patient receiving a high dose regimen for haematological malignancies has not been reported previously. We present one such case of methotrexate related acute lung injury in a patient of primary CNS lymphoma receiving high dose methotrexate.